2021
DOI: 10.1097/corr.0000000000001852
|View full text |Cite
|
Sign up to set email alerts
|

Collection and Reporting of Patient-reported Outcome Measures in Arthroplasty Registries: Multinational Survey and Recommendations

Abstract: This is a repository copy of Collection and reporting of patient-reported outcome measures in arthroplasty registries : multinational survey and recommendations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
49
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(56 citation statements)
references
References 45 publications
3
49
0
Order By: Relevance
“…4 the nonresponse rate that will invalidate the results of a study is unclear, 5 but a response rate of > 60% has been defined as acceptable by the international Society of arthroplasty Registries (iSaR) pROms working group. [3][4][5][6] the effect of non-response on data interpretation remains unclear. understanding the reasons for non-response is essential to both accurately interpret the data we do have and maximize response rates for the future.…”
Section: Introductionmentioning
confidence: 99%
“…4 the nonresponse rate that will invalidate the results of a study is unclear, 5 but a response rate of > 60% has been defined as acceptable by the international Society of arthroplasty Registries (iSaR) pROms working group. [3][4][5][6] the effect of non-response on data interpretation remains unclear. understanding the reasons for non-response is essential to both accurately interpret the data we do have and maximize response rates for the future.…”
Section: Introductionmentioning
confidence: 99%
“…Many papers assessed the physical functioning of patients undergoing hip replacement surgery using different patient-reported outcome measures. They provided a shortlist of the most promising generic and joint-specific instruments [4,5,11,12]. In Garnier et al [4], seventy-three studies were investigated, and 26 instruments were included, one of the most frequently assessed instruments being HHS.…”
Section: Discussionmentioning
confidence: 99%
“…Despite the increased interest in evaluating outcomes following hip arthroplasty, challenges remain in ensuring that such assessments of outcome are accurate, reliable, and relevant [4]. Generic patient-reported outcome measures describe a patient's global health status, and numerous comprehensive specific Patient-Reported Outcome Measures (PROMs) instruments are available for patients with hip problems [5]. Health-related quality-of-life data are valuable as they can provide relevant health-status information to health professionals and should be used as rationale for implementing the most adequate standard of health care [6].…”
Section: Introductionmentioning
confidence: 99%
“…12 ethical approval was not required since the data were deidentified and available in the public domain. this study is reported following the Reporting of studies Conducted using observational Routinely-collected data (ReCoRd) checklist, 15 and a checklist for transparent reporting of PRoMs from arthroplasty registries developed by Bohm et al 16 study dataset. the nhs PRoMs dataset includes patients undergoing nhs-funded primary hip and knee arthroplasty procedures in england from 1 april 2009 to 31 March 2020.…”
Section: Methodsmentioning
confidence: 99%